2007
DOI: 10.1017/s1368980007352518
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of heterocyclic amines in relation to socio-economic, lifestyle and other dietary factors: estimates in a Swedish population

Abstract: Objectives: To estimate the dietary intakes of heterocyclic amines (HCAs), to examine the intakes in relation to socio-economics, lifestyle and other dietary factors and to compare the classification of subjects by intake of HCA versus intake of meat and fish. Design: Cross-sectional analysis within the Malmö Diet and Cancer (MDC) cohort. Data were obtained from a modified diet history, a structured questionnaire on socioeconomics and lifestyle, anthropometric measurements and chemical analysis of HCAs. HCA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…The estimated daily intake of HA per capita from the analysis of the most-consumed meat dishes in a small population living in Spain, 285.6 ng, was higher than that estimated in Asian populations: 50 ng in China [43] and 72 ng in Japan [67], higher than the estimation carried out in Heidelberg (Germany), with 69 ng [68], but it was in the range of other European populations: 160 ng in Stockholm (Sweden) [26]; 690 ng in Malmö (Sweden) [69]; 330 ng in Switzerland [42]; 606 ng in Spain [29], and lower than in the United States: 1690 ng [70]; 455 ng [71]; 585 ng [72]; 715 -1293 ng [73], intakes estimated considering an average body mass of 65 kg. In this work, meat was the only source of HAs considered to estimate the daily intake of HAs per capita.…”
Section: Estimation Of Daily Ha Exposurecontrasting
confidence: 55%
“…The estimated daily intake of HA per capita from the analysis of the most-consumed meat dishes in a small population living in Spain, 285.6 ng, was higher than that estimated in Asian populations: 50 ng in China [43] and 72 ng in Japan [67], higher than the estimation carried out in Heidelberg (Germany), with 69 ng [68], but it was in the range of other European populations: 160 ng in Stockholm (Sweden) [26]; 690 ng in Malmö (Sweden) [69]; 330 ng in Switzerland [42]; 606 ng in Spain [29], and lower than in the United States: 1690 ng [70]; 455 ng [71]; 585 ng [72]; 715 -1293 ng [73], intakes estimated considering an average body mass of 65 kg. In this work, meat was the only source of HAs considered to estimate the daily intake of HAs per capita.…”
Section: Estimation Of Daily Ha Exposurecontrasting
confidence: 55%
“…For Asian populations: 50 ng in China (Wong et al, 2005) and 72 ng in Japan (Kobayashi et al, 2002) were estimated. In general, higher values have been found for European populations: 69 ng in Germany (Rohrmann et al, 2007); 160 ng , 690 ng (Ericson et al 2007) and 520 ng (Sonestedt et al, 2008) in Sweden; 330 ng in Switzerland (Zimmerli et al, 2001); and 286 ng and 606 ng in Spain (Busquets et al, 2004). Several studied performed in the United States studies found high values: 1.690 ng (Layton et al, 1995), 455 ng (Keating & Bogen, 2001), 585 ng (Bogen & Keating, 2001) and 715-1.293 ng (Keating & Bogen, 2004).…”
Section: Assessment Of the Exposure To Hcasmentioning
confidence: 95%
“…The amount of fat and the area-to-mass ratio may explain the observed differences; nevertheless, the cut of the samples was selected on the basis of ordinary consumption of each type of meat. Rohrmann and Becker (2002) reported average HA intake of 103 ng day -1 for the European population, but for the Swedish population Ericson et al (2007) reported 690 ng day -1 , which means 9-10 ng kg -1 day -1 . Estimations for the US population range from 11 to 20 ng kg -1 day -1 (Keating & Bogen 2004).…”
mentioning
confidence: 99%
“…Additionally, methods for dietary assessment and specific population dietary habits also affect the estimated carcinogens intake (Ericson et al 2007;Zheng & Lee 2009). The majority of epidemiological studies have shown that high intake of well-done meat and high exposure to meat carcinogens, particularly HAs, may increase the risk of human cancer.…”
mentioning
confidence: 99%